The Form and Meaning of Using Metaphors in Rusdin Tompo's Anthology of Mantera Cinta Poems (Stylistic Studies) - Dita Herlina Putri; Nensilianti Nensilianti; Faisal Faisal (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract.This The Use of Metaphors in the Anthology of  Mantera Cinta Poems by Rusdin Tompo (Stylistic Studies). This study aims to describe the form and meaning of the metaphors contained in the anthology of the analyzed poetry. This research is descriptive qualitative. The data used are words or groups of words that are shown as metaphors in the anthology of the poem Mantera Cinta by Rusdin Tompo. The data source used is the Anthology of Mantera Cinta Poetry by Rusdin Tompo. The approach used is Stylistics. The results of this study indicate that there are 3 out of 6 forms of using metaphors according to Enkvist, namely packages that wrap the core of pre-existing thoughts, choices between various existing statements, and deviations from norms and rules. The meaning contained in each poem was analyzed according to a keraf view. Based on this, it was found that the meaning of the use of metaphors in the poetry contained in Rusdin Tompo's anthology is an indirect meaning, then the dominant meaning of poetry is more directed to a man's love for his lover.Keywords: Metaphor, Stylistics, and Poetry